PENGARUH SISTEM AKUNTANSI KEUANGAN DAERAH, PENGELOLAAN KEUANGAN DAERAH, DAN GOOD GOVERNANCE TERHADAP KINERJA PEMERINTAH DAERAH (Studi Pada Satuan Kerja Perangkat Daerah Kota Pekanbaru) - Annisa, Vivid; Darlis, Edfan; ', Al Azhar A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to identify and analyze the effect of regional financial accounting system, financial management, and good governance on the performance of local government in the city of Pekanbaru. The population in this study are public servants of local government in the city of Pekanbaru SKPD consisting of 5 offices, 17 offices and 10 agencies. Mechanical sample selection using purposive sampling method. The sample in this study is the Head of Finance, Head of Programs and Staff Accounting / Finance, on the whole there were 3 respondents from each SKPD. So that the number of respondents in this study there were 96 respondents, but the amount of data that can be processed as many as 85 respondents. The data used is primary data sourced from respondents, with direct spreading questionnaire and analyzed using SPSS. Analysis of the data used in this study using multiple linear regression. The results of this study indicate that the area of financial accounting system, financial management and good governance on the performance of local government.Keywords: The area of financial accounting system, financial management, good governance, local government performa